Role of policy interventions in limiting emissions from vehicles in Delhi, 2020-2030 - Sanjib Pohit; Rishabh Singh; Soumi Roy Chowdhury (Asian Development Bank Institute (ADBI), 2021)
Urban India, particularly metros, is a major hotspot of air pollution with a PM2.5 concentration level ranging above the permissible limits defined by the WHO for most of the year. Unsurprisingly, special efforts have been made by the Government of India in recent years to improve air quality. Since the transport sector is a major source of air pollution in urban India, the Government of India adopted BS-VI emission standards in 2016 in principle for all major on-road vehicle categories. The rollout of Euro 6 in India began with the capital city Delhi. Furthermore, India's policymakers have been proactive in introducing clean fuel such as CNG, as well as electric vehicle and hydrogen fuel vehicles for urban transport. In this paper, we analyze the interplay between the policy shifts on transport and the level of emissions for Delhi for the next 10 years. We devised three scenarios, starting with the Optimistic Scenario (OPS), which assumes that all of the set policy targets of the Government of India will be realized as planned. A Pessimistic Scenario (PES) assumes implementation of the Optimistic Scenario with a delay of three years, and finally, the Business as Usual Scenario (BAU) assumes no policy interventions in the transport sector and a status quo to be in operation for the coming decade. We predict a significant decline in the emissions of particulate matter (PM), hydrocarbon (HC), carbon monoxide (CO), and nitrogen oxides (NOx) in the OPS/PES scenarios due to the proposed introduction of BS-VI and battery electric fuel vehicles. We find a 20.67% decrease in the overall PM emissions level in the city by 2030. By contrast, our BAU scenario predicts that emissions will increase significantly if no policy intervention is undertaken. In sum, policy interventions may lead to a substantial reduction in emissions in Delhi and thereby a longer life for Delhi inhabitants.
Keywords: F64; H23; I18; 330; air pollution; transport policy; auto industry; emissions; particulate matter; India